Азбука песен: [сборник] / Ю. Энтин - Энтин Юрий Сергеевич (Наши любимые мультфильмы, 2007)
Экземпляры: М/а ДБ (20081128) / Инвентарный номер: 92959 / Цена: 62.00 / Авт.знак: Э 67 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6